A response to the persistent digital divide: Critical components of a community network ecosystem. (November 2021) - Rich, Micaela Jordann; Pather, Shaun
The recent COVID-19 pandemic, and associated mitigation strategies of social distancing and self-isolation, has elevated the importance of telecommunications networks. In the current era there is little dispute amongst governments and at the highest levels of the United Nations in respect of the right of all citizens, regardless of their station in life, to have unfettered access to the Internet. However, despite substantive investments in telecommunications infrastructure development, a plethora of policy interventions and three world summits on the Information Society, more than half of the world's population remain unconnected. Over recent years, an emerging solution to the problem has been a bottom-up model of telecommunications ownership, referred to as community networks . There are varying approaches to community networks and different modes of implementation are observed across the globe. However, there is little evidence and consensus on what are all of the necessary elements of the system that comprise a successful community network. In light of this, this paper takes a first step towards the development of a comprehensive framework of the community network ecosystem. Based on the extant literature, a four-pronged People, Technology, Organization and Environment (PTOE) framework is derived. This is then subjected to qualitative analysis against descriptive reports of 11 existing community networks. The final framework and its sub-components provides a holistic and comprehensive perspective of the community network ecosystem. It serves as a basis for further analysis and research of community networks models and also as a means of informing practical implementation of both current and future community networks.